Case Report: Convalescent Plasma Therapy Induced Anti-SARS-CoV-2 T Cell Expansion, NK Cell Maturation and Virus Clearance in a B Cell Deficient Patient After CD19 CAR T Cell Therapy - Bošnjak, Berislav; Odak, Ivan; Ritter, Christiane; Stahl, Klaus; Graalmann, Theresa; Steinbrück, Lars; Blasczyk, Rainer; Falk, Christine S.; Schulz, Thomas F.; Wedemeyer, Hans Heinrich; Cornberg, Markus; Ganser, Arnold; et al. (Frontiers in Immunology, 2021)
Here, we described the case of a B cell-deficient patient after CD19 CAR-T cell therapy for refractory B cell Non-Hodgkin Lymphoma with protracted coronavirus disease 2019 (COVID-19). For weeks, this patient only inefficiently contained the virus while convalescent plasma transfusion correlated with virus clearance. Interestingly, following convalescent plasma therapy natural killer cells matured and virus-specific T cells expanded, presumably allowing virus clearance and recovery from the disease. Our findings, thus, suggest that convalescent plasma therapy can activate cellular immune responses to clear SARS-CoV-2 infections. If confirmed in larger clinical studies, these data could be of general importance for the treatment of COVID-19 patients.